Romania-China relations. Political and economic challenges in the BRI era - Liliana Popescu; Andreea Brînză (Romanian Journal of European Affairs)
Our paper explores the bilateral Romanian-Chinese relations, including the wider context of the EU-China relationship. There is a history to Romania-China relations, which favours Romania, given the closeness of the two countries during the Cold War period. The pursuit of EU membership by Romania contributed to a diminished attention paid to other parts of the world in the 2000s. This situation is changing. The EU membership enrolled Romania in common EU policies, including trade policy. The EU-China relations developed visibly, particularly after 2003; a renewed impetus is noticeable starting with 2009, and again in 2013. Romania’s renewed interest and opening towards China coincides with the year when the Belt and Road Initiative (BRI) was launched. Even though there were cancellations and delays in implementing certain common projects, there are good prospects for improvement and new openings.